Mulberry Anthocyanin Extract Ameliorates Oxidative Damage in HepG2 Cells and Prolongs the Lifespan of Caenorhabditis elegans through MAPK and Nrf2 Pathways. (21st June 2017) - Yan, Fujie; Chen, Yushu; Azat, Ramila; Zheng, Xiaodong
Abstract : Mulberry anthocyanins possess many pharmacological effects including liver protection, anti-inflammation, and anticancer. The aim of this study was to evaluate whether mulberry anthocyanin extract (MAE) exerts beneficial effects against oxidative stress damage in HepG2 cells and Caenorhabditis elegans. In vitro, MAE prevented cytotoxicity, increased glucose consumption and uptake, and eliminated excessive intracellular free radicals in H2 O2 -induced cells. Moreover, MAE pretreatment maintained Nrf2, HO-1, and p38 MAPK stimulation and abolished upregulation of p-JNK, FOXO1, and PGC-1 α that were involved in oxidative stress and insulin signalling modulation. In vivo, extended lifespan was observed in C. elegans damaged by paraquat in the presence of MAE, while these beneficial effects were disappeared in pmk-1 and daf-16 mutants. PMK-1 and SKN-1 were activated after exposure to paraquat and MAE suppressed PMK-1 activation but enhanced SKN-1 stimulation. Our findings suggested that MAE recovered redox status in HepG2 cells and C. elegans that suffered from oxidative stress, which might be by targeting MAPKs and Nrf2.